Behavior of the housing market around a macro urban project: Heritage neighborhoods of Pichincha and Refinería in Rosario (ARQUISUR Revista, 2017)
The research focuses on the economic impact generated by the large urban project in Puerto Norteits Refinería and Pichincha surrounding neighborhoods in the city of Rosario.The goal then is to analyze production processes and recovery of these two historic districts, which had little vacant land and valued. To do lots and old houses that are offered are described, increased demand, new local agents involved, the types of sub–markets and prices of land and property, expressing the various forms of speculation. The main results show that Pichincha had a previous building development at the beginning of his works and larger while Refinería suffered less impact but directly linked to Puerto Norte. The higher valuation is established in the avenues, directly related to the location and regulatory change.
Keywords: real estate; urban recovery; economic impact; major urban project; patrimonials surrounding neighborhoods